Brix refractometry in serum as a measure of failure of passive transfer compared to measured immunoglobulin G and total protein by refractometry in serum from dairy calves. (May 2016) - Hernandez, D.; Nydam, D.V.; Godden, S.M.; Bristol, L.S.; Kryzer, A.; Ranum, J.; Schaefer, D.
Highlights: We evaluated Brix refractometry for the assessment of failure of passive transfer in dairy calves. Brix refractometry can estimate serum IgG determined by immunoassays. Brix refractometry can evaluate three key indicators in calf rearing: colostrum quality, milk solids, and passive transfer. Abstract: A series of trials were conducted to evaluate Brix refractometry (Brix %) for the assessment of failure of passive transfer (FPT) in dairy calves compared to: (1) serum IgG (reference standard) when measured by radial immunodiffusion (RID) or a turbidometric immunoassay (TIA), and (2) serum total protein refractometry (STP). For the serum samples tested with TIA, STP, and Brix % ( n  = 310; Holstein calves), the median concentrations were 21.3 g/L IgG, 58 g/L STP, and 9.2%, respectively. For the serum samples tested with RID, STP and Brix % ( n  = 112; Jersey calves), the mean concentrations were 38 g/L IgG, 68 g/L STP, and 10.2%, respectively. For samples tested with only Brix % and STP ( n  = 265; Holstein calves), median STP and Brix % were 50 g/L STP and 8.5%, respectively. Correlations between Brix % and RID, and between Brix % and TIA were equal ( r  = 0.79, respectively). Brix % and STP were positively correlated ( r  = 0.99). Brix % estimated serum IgG concentrations determined by TIA and RID ( r 2  = 0.63, 0.62, respectively). When FPT was defined as serum IgG < 10 g/L, Brix % ≤ 8.5% showed optimal sensitivity (100%) and specificity (89.2%) to predict FPT. At the same IgG cut-point, an STP value of ≤ 52 g/L showed a similar sensitivity (100%) and specificity (80.4%) to predict FPT. Brix refractometry predicted successful transfer of passive immunity in dairy calves, but further evaluation as a diagnostic tool for the diagnosis of FPT is warranted.